Fish and the Thyroid: A Janus Bifrons Relationship Caused by Pollutants and the Omega-3 Polyunsaturated Fatty Acids - Benvenga, Salvatore; Famà, Fausto; Perdichizzi, Laura Giovanna; Antonelli, Alessandro; Brenta, Gabriela; Vermiglio, Francesco; Moleti, Mariacarla (Frontiers in Endocrinology, 2022)
Benefits of the omega-3 polyunsaturated fatty acids (PUFA) on a number of clinical disorders, including autoimmune diseases, are widely reported in the literature. One major dietary source of PUFA are fish, particularly the small oily fish, like anchovy, sardine, mackerel and others. Unfortunately, fish (particularly the large, top-predator fish like swordfish) are also a source of pollutants, including the heavy metals. One relevant heavy metal is mercury, a known environmental trigger of autoimmunity that is measurable inside the thyroid. There are a number of interactions between the omega-3 PUFA and thyroid hormones, even at the level of the thyroid hormone transport proteins. Concerning the mechanisms behind the protection from/amelioration of autoimmune diseases, including thyroiditis, that are caused by the omega-3 PUFA, one can be the decreased production of chemokines, a decrease that was reported in the literature for other nutraceuticals. Recent studies point also to the involvement of resolvins. The intracellular increase in resolvins is associated with the tissue protection from inflammation that was observed in experimental animals after coadministration of omega-3 PUFA and thyroid hormone. After having presented data on fish consumption at the beginning, we conclude our review by presenting data on the market of the dietary supplements/nutraceuticals. The global omega-3 products market was valued at USD 2.10 billion in 2020, and was projected to go up at a compound annual growth rate of 7.8% from 2020 to 2028. Among supplements, fish oils, which are derived mainly from anchovies, are considered the best and generally safest source of omega-3. Taking into account (i) the anti-autoimmunity and anti-cancer properties of the omega-3 PUFA, (ii) the increasing incidence of both autoimmune thyroiditis and thyroid cancer worldwide, (iii) the predisposing role for thyroid cancer exerted by autoimmune thyroiditis, and (iv) the risk for developing metabolic and cardiovascular disorders conferred by both elevated/trendwise elevated serum TSH levels and thyroid autoimmunity, then there is enough rationale for the omega-3 PUFA as measures to contrast the appearance and/or duration of Hashimoto’s thyroiditis as well as to correct the slightly elevated serum TSH levels of subclinical hypothyroidism.